A bionic solution to make cement matrix tough. (February 2023) - Pan, Hao; Geng, Zifan; Huang, Peng; Zhou, Yang; Tang, Jinhui; She, Wei; Liu, Jiaping
Abstract: Toughening of cement matrix without fiber has become a great puzzle to be addressed. Conventional polymer-modification methods show the limited toughening effect and the brittle fracture mode has not been altered. Herein, a nacre-inspired solution is proposed to make cement matrix tough by constructing a special "brick-and-mortar" structure which is applicable for cementitious system, and using two polymers to provide the intrinsic and extrinsic toughening effect, respectively. Non-traditional fabrication methods including shearing, granulation, and hot-pressing are adopted to implement the design. The flexural performance and microstructure of untoughened and differently toughened matrixes are investigated to reveal the toughening mechanisms and prove the effectiveness of the proposed strategy. Compared with the untoughened matrix, the toughened matrix through bionic method demonstrates a graceful ductile fracture, and acheives a 323% toughness enhancement while maintains 90% of flexural strength. This work offers prospects for toughening of cement-based materials via bionic approaches.